A Two Step Emperical Method for the Determination of Effective Thermal Conductivity of Multi-Phase Porous Solids - Shabbir, G. (The Nucleus, 2020)
A two step empirical approach is proposed to estimate the effective thermal conductivity of porous solids. The total thermal conductivity of solid phase is calculated by assuming different minerals arranged in â€œparallelâ€. Then the final effective thermal conductivity is calculated by taking in to account the porosity content and an additional empirical parameter related to geometry of pore. It is shown that the effective thermal conductivity of a porous rock can be successfully modeled from the thermal conductivity of constituent mineral phases determined by x-ray diffraction and porosity measurements by standard methods.